Exploring the Antioxidant and Neuroprotective Potential of Muscari armeniacum: Phenolic Profiling and Enzyme Inhibition - Fevzi Topal; Firat Yılmaz; Meryem Topal; Ahmed Menevşeoğlu (Turkish Journal of Agriculture: Food Science and Technology)
This study aimed to investigate the antioxidant and enzyme inhibitory properties of Muscari armeniacum, a plant native to Türkiye, which is known for its bioactive compound content. Ethanol extracts of Muscari armeniacum were prepared and analyzed using a variety of bioanalytical methods to assess its potential health-promoting properties. The antioxidant capacity was evaluated through Fe³⁺-Fe²⁺ reduction capacity, CUPRAC, DPPH, and ABTS radical scavenging activities. Additionally, the total phenolic and flavonoid contents of the extracts were determined, as these compounds are critical indicators of antioxidant potential. The antioxidant activity of Muscari armeniacum was compared with five standard antioxidants commonly used for benchmarking: BHA, α-tocopherol, BHT, trolox, and ascorbic acid. The extract demonstrated a high flavonoid content (23.24 µg QE/mg extract) and a significant amount of phenolics (14.38 µg GAE/mg extract), with the flavonoid content being particularly noteworthy. In addition to its antioxidant properties, the enzymatic activity assays revealed that the extract significantly inhibited acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes, which are associated with neurodegenerative diseases such as Alzheimer’s. The IC₅₀ values were determined to be 54.14 mg/mL (R² = 0.9695) for AChE and 58.73 mg/mL (R² = 0.9609) for BChE, indicating moderate enzyme inhibition. These results suggest that Muscari armeniacum could serve as a valuable source of bioactive compounds with significant antioxidant and enzyme inhibitory activities. Its potential applications in the treatment of oxidative stress-related diseases and neurodegenerative disorders make it a promising candidate for further pharmacological studies. This research underscores the importance of exploring native plants for their medicinal and therapeutic potential, contributing to the development of alternative treatments for challenging health conditions.